Agile legged locomotion in reconfigurable modular robots - Chen Yu; David Matthews; Jingxian Wang; Jing Gu; Douglas Blackiston; Michael Rubenstein; Sam Kriegman (Proceedings of the National Academy of Sciences, 2026)
Legged machines are becoming increasingly agile and adaptive, but they have so far lacked the morphological diversity of legged animals, which have been rearranged and reshaped to fill millions of niches. Unlike their biological counterparts, legged machines have largely converged over the past decade to canonical quadrupedal and bipedal architectures that cannot be easily reconfigured to meet new tasks or recover from injury. Here, we introduce autonomous modular legs: agile yet minimal, single-degree-of-freedom jointed links that can learn complex dynamic behaviors and may be freely attached to form multilegged machines at the meter scale. This enables rapid repair, redesign, and recombination of highly dynamic modular agents that move quickly and acrobatically (nonquasistatically) through unstructured environments. Because each module is itself a complete agent, the bodies that contain them can sustain deep structural damage that would completely disable other legged robots. We also show how to encode the vast space of possible body configurations into a compact latent design space that can be efficiently explored, revealing a wide diversity of novel legged forms.